Using quinine as a fluorescent tracer to estimate overland flow velocities on bare soil: Proof of concept under controlled laboratory conditions - de Lima, João L. M. P. (2021)
This study presents a tracer technique based on the fluorescent properties of quinine to help on the visualization of shallow flows and allow a quantitative measurement of overland flow velocities. Laboratory experiments were conducted to compare the traditional dye tracer and thermal tracer techniques with this novel fluorescent (quinine) tracer by injecting a quinine solution and the other tracers into shallow flowing surface water. The leading-edge tracer velocities, estimated using videos of the experiments with the quinine tracer were compared with the velocities obtained by using thermograms and real imaging videos of the dye tracers. The results show that the quinine tracer can be used to estimate both overland and rill flow velocities, since measurements are similar to those resulting from using other commonly used tracers. The main advantage of using the quinine tracer is the higher visibility of the injected tracer under ultraviolet A (UVA) light for low luminosity conditions. In addition, smaller amounts of quinine tracer are needed than for dye tracers, which lead to smaller disturbances in the flow. It requires a simple experimental setup and is non-toxic to the environment.